The following sequence converging to Gelfond's constant ($e^\pi$) is apparently mentioned (and originates?) in the book "Mathematics by Experiment: Plausible Reasoning in the 21st Century.", which I unfortunately do not have access to. $$k_0 = 1/\sqrt{2},\quad k_{n+1}={\frac {1-{\sqrt {1-k_{n}^{2}}}} {1+{\sqrt {1-k_{n}^{2}}}}}$$ $$e^\pi =\lim_{n\to\infty} \left(\frac{4}{k_{n+1}}\right)^{2^{-n}}$$ How is this sequence and similar ones derived?

  • 1
    $\begingroup$ The algorithm above appears at page 137 of Mathematics by Experiment, but no proof is given there either. $\endgroup$ – Jack D'Aurizio Oct 25 '17 at 23:45
  • 2
    $\begingroup$ Anyway, it is not difficult to guess that such algorithm is related to $e^{\pi K'/K}$ and to the fact that $\frac{1}{\sqrt{2}}$ is an elliptic singular value, hence it turns out to be a minor twist on the classical AGM algorithm for the computation of $K(k)$. I will write a detailed answer tomorrow, if no one comes before me. Time to sleep in Italy, have a good night. $\endgroup$ – Jack D'Aurizio Oct 25 '17 at 23:59

As mentioned in comments (to the question) from Jack d'Aurizio this is related to elliptic integrals. And based on the feedback received in comments to this answer I provide some background in the theory of elliptic integrals and theta functions. The details along with proofs are available in the linked blog posts.

Let $k\in(0,1)$ be the elliptic modulus and then we define complementary modulus $k'=\sqrt{1-k^{2}}$. Further the complete elliptic integrals of the first kind are defined by $$K(k)=\int_{0}^{\pi/2}\frac{dx}{\sqrt{1-k^{2}\sin^{2}x}},\, K'(k)=K(k')\tag{1}$$ By the way the use of prime $(') $ here does not denote derivative.

Starting with a modulus $k$ we define a new modulus $l$ via ascending Landen transformation $$l=\frac{2\sqrt{k}}{1+k},\,k=\frac{1-l'}{1+l'},\, l>k\tag{2}$$ where $l'$ is complementary to $l$ ie $l'=\sqrt{1-l^{2}}$. It can be proved with some effort that $$K(l)=(1+k) K(k)$$ Using a little amount of algebra it can be seen that the relation between $l$ and $k$ is same as the relation between $k'$ and $l'$ and hence from the above equation we get $$K'(k) =(1+l') K'(l)=\frac{2K'(l)}{1+k}$$ and therefore from the last two equations we get $$\frac{K'(k)} {K(k)} =2\cdot\frac{K'(l)}{K(l)}\tag{3}$$ Corresponding to elliptic modulus $k$ we have another variable $q$ called nome defined by $q=\exp(-\pi K'(k) /K(k)) $ and it is possible to get an expression for $k$ in terms of $q$ via the use of theta functions. We have $$k=\frac{\vartheta_{2}^{2}(q)}{\vartheta_{3}^{2}(q)}\tag{4}$$ where $$\vartheta_{2}(q)=2q^{1/4}\sum_{n=0}^{\infty}q^{n(n+1)},\,\vartheta_{3}(q)=1+2\sum_{n=1}^{\infty}q^{n^{2}}\tag{5}$$

The sequence $k_{n} $ in question is descending Landen sequence of elliptic moduli and using equation $(3)$ we have $$\frac{K'(k_{n+1})}{K(k_{n+1})}=2\cdot\frac{K'(k_{n})}{K(k_{n})},\, K'(k_{0})=K(k_{0})\tag{6}$$ The corresponding nomes $q_{n} =\exp(-\pi K'(k_{n}) /K(k_{n})) $ have a relation between them as $q_{n+1}=q_{n}^{2}$. Thus we can see that $$e^{-\pi}=q_{0}=(q_{n})^{2^{-n}}\tag{7}$$ Next also note that $q_{n} \to 0, k_{n} \to 0$ as $n\to \infty$ and using $(4)$ we have the relation $$\lim_{n\to\infty}\frac{k_{n}^{2}}{16q_{n}}= 1\tag{8}$$ (the above equation can also be proved without using the theory of theta function via the fundamental asymptotic $K'(k) =\log(4/k)+o(1)$ as $k\to 0^{+}$). The desired relation follows easily from $(7)$ and $(8)$ and the relation $k_{n} ^{2}=4k_{n+1}/(1+k_{n+1})^{2}$.

  • $\begingroup$ Do you think I understand anything of what you wrote ? $\endgroup$ – reuns Oct 29 '17 at 13:50
  • $\begingroup$ Thank you! Could add some more detail for those who aren't familiar with the topic? (e.g. What's a Landen sequence? How do we get the value of the limit?) $\endgroup$ – nbubis Oct 29 '17 at 16:29
  • $\begingroup$ @reuns : I will add some more details, but let me know specific areas which you find need explanation. $\endgroup$ – Paramanand Singh Oct 29 '17 at 16:43
  • $\begingroup$ @nbubis: will add more details, wait for sometime. $\endgroup$ – Paramanand Singh Oct 29 '17 at 16:46
  • $\begingroup$ I can't even explain what I want explanations on, honestly this is just a mess of symbols without any explanation. In the theory of elliptic integrals and functions there is a lattice and an associated cubic polynomial with some special functions (and their inverse functions) attached to it. $\endgroup$ – reuns Oct 29 '17 at 16:52

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.